Graphene inclusion effect on anion-exchange membranes properties for alkaline water electrolyzers. (10th July 2020) - Ion-Ebrasu, Daniela; Pollet, Bruno G.; Caprarescu, Simona; Chitu, Alin; Trusca, Roxana; Niculescu, Violeta; Gabor, Raluca; Carcadea, Elena; Varlam, Mihai; Vasile, Bogdan Stefan
Abstract: The main issues facing the development of Anion Exchange Membranes (AEM) are the low hydroxide ion (OH − ) conductivity compared to protons (H + ), and the thermal and chemical stability. Based on the its unique two-dimensional structure, graphene is estimated to be one of the best solutions for the hydrogen ions (H + and OH − ) selectivity and conductivity improvement. This work presents the graphene-composite membranes (AEMGrs) preparation and characterization in comparison with commercial FAA3-20® and FAA3-30® membranes from Fumatech. Various amounts of commercial graphene were incorporated into the Fumion® FAA-3 in NMP (10%), solutions which were then used to fabricate new AEMs by the Doctor-Blade (DB) method. Commercial and graphene-composite AEMs were studied by infrared spectroscopy with Fourier Transformation (FTIR), thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC), scanning electron microscopy (SEM), dynamic mechanical analysis (DMA), water uptake (WU), ion exchange capacity (IEC), and in plane four-points electrochemical impedance spectroscopy (4p-EIS). The results indicated that the composite membranes containing 50 mg of graphene exhibited an improved IEC (3.16 mmol g −1 ) and OH − conductivity (113.27 mS cm −1 ) at 80 °C measured in 0.01 M KOH (pH = 12). Highlights: One-phase procedure for Anion Exchange Graphene Composite Membranes development is described. The graphene nanoparticles increase the composite membranes stiffness and the thermal stability. The composite membranes OH -  conductivity increases with graphene concentration and temperature.